Contemporary legends from Tuva - Oelschlägel, Anett K. (The New Research of Tuva, 2012)
Author analyzes the results of her field work in Tuva during 2004-2005 collecting contemporary Tuvan legends. She defines the term "contemporary legends”, it’s characteristics and compares with similar German texts.